Metal-free photocatalytic trifluoromethylative pyridylation of unactivated alkenes. Issue 22 (24th October 2018) - He, Yu-Tao; Kang, Dahye; Kim, Inwon; Hong, Sungwoo
Abstract : An efficient, transition metal-free trifluoromethylative pyridylation of unactivated alkenes was achieved by visible-light-induced photoredox catalysis. Abstract : An efficient, transition metal-free trifluoromethylative pyridylation of unactivated alkenes was achieved by visible-light-induced photoredox catalysis employing CF3 SO2 Na and a pyridinium salt in the presence of eosin Y as a photoredox catalyst. The overall process is thought to occur by the selective addition of an electrophilic CF3 radical to the alkene substrate to provide an alkyl radical intermediate, which subsequently engages in an addition to the pyridinium salt. This three-component photocatalytic strategy circumvents traditional multistep procedures and readily affords synthetically and biologically important trifluoromethyl- and pyridyl-containing frameworks.